Basketball (and other things) a collection of questions asked, answered, illustrated - Serrano, Shea (Abrams Image, 2017)
"Thirty-three chapters, each chapter a different basketball question that needs to be answered. Some of them are obviously crucial ... and some of them are secretly crucial. But all of them are approached in ways that ([the author] hope[s] you think) are smart and fun and nuanced"--Back cover.